TINJAUAN YURIDIS TERHADAP AKIBAT HUKUM JAMINAN FIDUSIA YANG BELUM DI DAFTARKAN TERHADAP PEMINJAMAN KREDIT PADA BANK - Riza Ayu Anggraini, Ni Putu; Sudiarta, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013)
In writing imliah work entitled "Against Judicial Review Due Fiduciary Law OfThe Not Registered Loan Credit In Bank". Writing method used in this paper is thenormative. Issues raised in this paper is how the legal consequences if the fiduciary hasnot been registered, then made the binder as a credit on bank lending and how in thefuture if the credit had not been paid, and the debtor's death, while the fiduciary has notbeen registered, what the consequences are acceptable by the bank as the lender. Basedon research conducted in accordance with the result that the mandate of fiduciary law,to receive legal protection as stipulated in the law fiduciary, loading objects fiduciarydeed must be made by authentic act and recorded in the Register of fiduciary. If theterms are not met, the rights of creditors do not receive protection as mentioned infiduciary law. While the fiduciary has not been registered, in effect, the agreementsprovide fiduciary assurance under the hand can not be executed immediately.
Keywords: Judicial Review, Legal Consequences, Credit, Bank